Poynting Vector Streamlines and the Marine Controlled Source Electromagnetic Airwave - Pethick, Andrew; Harris, Brett (EAGE, 2013)
We investigate the airwave using streamline visualization of the Poynting vector. The airwave is a principal feature of marine controlled source electromagnetic surveys. The airwave is in no doubt a complex interaction with the all the geo-electrical elements; the highly resistive air, conductive seawater column and sub-ocean sediments and hydrocarbons all influence its signature. The number of published descriptions and seemingly contradictory explanations may have led to confusion over its physical reality. The airwave has been described mathematically, as an analogy to refraction seismic and as a downwardly diffusing wave. We use Poynting vector streamlines to determine the best airwave representation. The airwave is seen as a downwardly diffusing vortex when visualised by field vector streamlines. The airwave presents differently in the Poynting vector streamlines. The energy flows vertically upwards from the transmitter, "refracts” along the air-ocean interface and down towards the ocean floor. The energy flowing upwards from the earth interacts with this downwardly flowing energy to form an airwave front